Performance evaluation of prefabricated polyvinyl chloride floating dome type anaerobic biogas digester of different feeding intervals using animal waste. Issue 1 (8th December 2021) - Haque, Mohammad Enamul; Ryndin, Roman; Mang, Heinz‐Peter; Kabir, Humayun; Rahman, Mohummad Muklesur; Khasruzzaman, Abul Kalam Mohammad; Uddin, Mohammad Asir; Islam, Mohammad Alimul
Abstract: Background: Anaerobic digestion (AD) has many benefits and is a safe way to generate energy, address the energy shortage problem, and reduce waste and carbon emissions. The study aimed to determine the performance evaluation of prefabricated polyvinyl chloride (PVC) biogas digester and compare different feeding intervals using cow manure. This study was conducted at ambient temperature in three types of feeding practice (daily, 4‐day, and 7‐day feeding interval) to investigate the variation of biogas production and evaluation of digester performances. The composition of biogas, pH, and total volatile fatty acids (TVFA) were measured regularly and weekly basis. The TVC, Escherichia coli, and Salmonella spp. counts were determined by the spread plate technique method using PCA, EMB agar, and SS agar plate, respectively. Results: The comparison results of daily versus 4‐day feeding interval indicated that the total biogas and methane yield was 34% and 28% higher in 4‐day interval feeding. The average digester performance was also 34% higher in 4‐day feeding interval digester than daily feeding digester. However, the comparison results of daily versus 7‐day interval feeding indicated that the total biogas, methane yield, and digester performance were slightly higher in daily feeding. Before and after AD, the bacterial load (TVC, E. coli, and Salmonella spp. count) was reduced by 2–3 logs, and this reduction was also statistically significant ( p < 0.05). Conclusion: The performance of PVC digester was highly satisfactory and good enough to fulfil the demand (0.8–1.6 m 3 ) of a five‐member family for cooking both in urban and rural areas of Bangladesh.